Development of an Adaptive Outcome-Based Education Learning Model Integrating Merdeka Belajar Kampus Merdeka in Post-Disaster Higher Education - Wiwik Gusnita; Titen Darlis Santi; Ade Irferamuna (Postgraduate, University of Mataram, 2026)
This objective of study is adaptive Outcome-Based Education (OBE) model integrated with the Merdeka Belajar Kampus Merdeka (MBKM) policy to address learning needs in post-disaster areas of West Sumatra. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Participants included lecturers, Culinary Education students, and MBKM partners involved in humanitarian projects. Data were collected through interviews, observations, and Course Learning Outcome (CLO) assessments. The results indicate that experts rated the model as highly feasible with a validity score of 88.67%. Adaptation is specifically achieved through a flexible hybrid curriculum and direct student involvement in community economic recovery via culinary-based humanitarian projects. Model effectiveness was confirmed by a significant increase in average CLO achievement from 71.74 to 87.72%, with a moderate N-gain of 0.56 (p< 0.05). This study concludes that the adaptive OBE-MBKM model serves as an effective instructional innovation for post-disaster higher education. It successfully aligns academic competencies with community-based disaster resilience, providing a strategic framework for culinary education to contribute directly to regional recovery and social responsiveness. This model offers a replicable approach for higher education institutions operating in disaster-prone regions to maintain academic quality while fostering social impact.